An analytical study of active earth pressure in cohesive soil considering interlayer shear stress - Qizhuo Liu; Tianci Zhong; Daocai Li; Yuanyuan Duan (PLoS ONE, 2025)
The impact of interlayer shear stress on the distribution of earth pressure in cohesive soil is notable, but currently, there lacks a comprehensive theory that integrates this factor in the calculation of active earth pressure. Drawing from the Mohr stress circle specific to clay soils, a formula to calculate interlayer shear stress has been derived. Moreover, a robust model has been formulated to compute the active earth pressure in clay soils, incorporating elements such as interlayer shear stress, effects of displacement, soil arching, and the morphology of the sliding surface. To address the challenge of integrating interlayer shear stress in clay soils for an explicit solution, a numerical iteration framework was developed. This framework facilitates the calculation of the strength, resultant force, and point of action for the active earth pressure in cohesive soil. The efficacy of this solution was evaluated by comparing it with the Rankine solution, other existing analytical solutions, and outcomes from standard model tests. Notably, when compared with the experimental findings of the word previous study, this new method exhibited a higher congruence, with discrepancies no greater than 9.8%. This indicates a significant enhancement in accuracy, providing a methodological advancement in calculating earth pressure from static to ultimate active states, inclusive of non-limit active earth pressure during controlled wall displacement scenarios. This novel approach not only supplements but also refines the theoretical framework for earth pressure calculations, offering a more precise computational tool for practical engineering applications.